PENGARUH PENAMBAHAN ASAM ASKORBAT TERHADAP SIFAT FUNGSIONAL PATI UBI JALAR UNGU (Ipomea batatas L.): (The Effect of Ascorbic Acid Addition on Functional Characteristic of Purple Sweet Potato (Ipomea batatas L.) Starch) - Amran Laga; Tuflika Primi Putri; Adiansyah Syarifuddin; Nuril Hidayah; Muhpidah Muhpidah (Hasanuddin University Food Science and Technology Study Program, 2019)
Purple sweet potato starch is known for its anthocyanin content and has a high carbohydrate content, especially starch. Starch extraction in purple sweet potato can cause browning due to the presence of PPO enzymes which results in decreased anthocyanin content in the resulting starch. Ascorbic acid can be used as an anti-browning agent. The analysis results obtained are the drying of purple sweet potato starch can be done for 4 hours because at that time the water content has been constant for a long time of further drying. The anthocyanin content of purple sweet potato starch decreases with increasing concentration of the addition of ascorbic acid, but the addition of ascorbic acid causes an increase in antioxidants of purple sweet potato starch because ascorbic acid is one type of antioxidant